2014
DOI: 10.1116/1.4899181
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study on room-temperature atomic layer deposition of HfO2 using tetrakis(ethylmethylamino)hafnium and remote plasma-excited oxidizing agents

Abstract: Room-temperature atomic layer deposition (ALD) of HfO2 was examined using tetrakis (ethylmethylamino)hafnium (TEMAH) and remote plasma-excited water and oxygen. A growth rate of 0.26 nm/cycle at room temperature was achieved, and the TEMAH adsorption and its oxidization on HfO2 were investigated by multiple internal reflection infrared absorption spectroscopy. It was observed that saturated adsorption of TEMAH occurs at exposures of ∼1 × 105 L (1 L = 1 × 10−6 Torr s) at room temperature, and the use of remote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In our previous study, the room-temperature HfO 2 ALD was developed by using TEMAH and the plasma excited humidified oxygen (water vapor and oxygen) [20]. In this study, it was reported that TEMAH, having a similar chemical structure to TEMAZ, has a saturation behavior on hydroxylated HfO 2 surfaces with its exposure of 1.0 ×10 5 L. We can say that TEMAZ and TEMAH have almost the same adsorption characteristics in RT ALD.…”
Section: -3 Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In our previous study, the room-temperature HfO 2 ALD was developed by using TEMAH and the plasma excited humidified oxygen (water vapor and oxygen) [20]. In this study, it was reported that TEMAH, having a similar chemical structure to TEMAZ, has a saturation behavior on hydroxylated HfO 2 surfaces with its exposure of 1.0 ×10 5 L. We can say that TEMAZ and TEMAH have almost the same adsorption characteristics in RT ALD.…”
Section: -3 Discussionmentioning
confidence: 81%
“…As we can see in the previous studies for the adsorption sites [19,20], the hydroxyl groups are expected as the adsorption sites. We monitored the absorbance of the surface hydroxyl group by MIR-IRAS for the TEMAZ and plasma treatments as shown in Fig.…”
Section: -1 Reaction Mechanismmentioning
confidence: 89%
See 3 more Smart Citations